An Analysis of English Language Teaching Activities during Covid-19 Pandemic at SMP Purnama Jakarta - Yulia Firza Safira; Muhamad Sofian Hadi; Zaitun Zaitun (Journal of Languages and Language Teaching, 2021)
This study was led to know the activities of English teaching during the COVID-19 pandemic at SMP Purnama Jakarta. This study utilized a qualitative descriptive method, while the information assortment methods utilized interviews, observation, and documentation. Interviews were led with an English teacher who teaches at SMP Purnama Jakarta, while polls were given to a few students at SMP Purnama Jakarta. The subjects of this investigation were an English teacher and a few students at SMP Purnama Jakarta. The outcomes show that learning during the pandemic is way different from the regular learning (in-person) that was done before the COVID-19 pandemic. The distinction that can be seen is that the instructional framework, which was initially up in-person, turned out to be totally internet or technology-based by utilizing Google Meet, Google Classrooms, WhatsApp, YouTube, and other applications.